Heterosis en líneas F1 derivadas de cruzamientos entre el progenitor FE-103-UTB con 11 genotipos de Arroz (Oryza sativa L. spp. indica) - Pilco Moyota, Alex Orlando (2019)
This experimental work was carried out at the El Palmar Experimental Farm of the Technical University of Babahoyo, CEDEGE Project, and belonging to the province of Los Ríos. Located at Km 12 of the Babahoyo - Montalvo road; with the geographical coordinates UTM: X = (-1.806238) south latitude, Y = (-79.519417); Western length, at 17 meters above sea level. The objectives were as follows: Analyze the heterotic index on phenotypic characters of F1 progenies derived from crosses between the parents FE-103-UTB with 11 rice cultivars. Evaluate and select outstanding heterotic progenies of F1 populations. Identify progenies with the best agronomic and production characteristics. It was used as planting material 22 segregating populations F1 of índicatype rice, obtained by the Biotechnology Laboratory of the Technical University of Babahoyo from direct and reciprocal crosses using the FE-103-UTB line, both as a female and male parent in combination with 11 different genotypes of índica rice. As a statistical method the measures of central tendency (mean and mode), dispersion measures (variance and standard deviation) were used, in addition; frequency histogram distribution tables and / or frequency polygons were made. The estimation of Heterosis (H) or Hybrid vigor was performed based on formula H = (F1- (P1 + P2) / 2) / ((P1 + P2) / 2) x 100. Seventeen evaluations were carried out as: plant height at 20, 40, 60, and 80 days after transplant, vigor, length and width of flag leaf, days to flowering, vegetative cycle, panicle length, tillers / plant, panicle / plant, grains / panicle, 1000 grain weight, plant / grain yield (g), shelling,% sterility, grain length and width, and grain shape. From the results obtained, it was determined that in the variables: days to flowering and vegetative cycle, five early populations were obtained from the crossings: FI-106 / FE-103, FE-103 / BA-100, FE-103 / FI.105, FE-103 / FI-107, FI-107 / FE-103, highlighting the progeny of the cross FI-106 / FE-103 upon reaching a flowering at 84 days and a vegetative cycle of 114 days. According to the production variables analyzed, such as number of tillers per plant, number of panicles per plant, number of grains per panicle, weight of one thousand grains and grain yield per plant, line F1 corresponding to the SH-108 / junction was highlighted. FE-103 with outstanding values in the variables considered as performance components. The progenies, SH-108 / FE-103 and FE-103 / FI-105, could be identified, with the best phenotypic, agronomic and production characteristics, presenting outstanding heterotic values in the variables number of tillers per plant, number of panicles per plant, panicle length, number of grains per panicle and grain yield per plant.